Evaluasi Kewajiban Perpajakan Bendahara Universitas Papua Atas Pemotongan/Pemungutan PPh Atas Belanja Modal Tahun 2023 - Nurrohman, Pungkas; Rahmawati, Ulfa (Jurnal Akuntansi Terapan dan Bisnis, 2024)
The state treasurer plays an important role in implementing tax obligations related to the use of the APBN/APBD. This study explains the suitability of the implementation of tax obligations by the Treasurer of the University of Papua for PPh capital expenditure in 2023 when compared to applicable provisions. The researcher used a descriptive qualitative method. The results of the study indicate that the implementation of capital expenditure tax obligations is not fully in accordance with the provisions. Based on the results of the study, it is expected that the Manokwari Pratama Tax Office will provide counseling regarding the renewal of tax provisions to treasurers. In addition, the Pratama Tax Office needs to provide counseling for treasurers who do not understand the new tax provisions. Meanwhile, the University of Papua needs to create a forum with the Manokwari Pratama Tax Office in implementing SOPs for financial transactions with other parties.